2022
DOI: 10.7554/elife.66080
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fluorescence lifetime imaging of macrophage intracellular metabolism during wound responses in zebrafish

Abstract: The function of macrophages in vitro is linked to their metabolic rewiring. However, macrophage metabolism remains poorly characterized in situ. Here, we used two-photon intensity and lifetime imaging of autofluorescent metabolic coenzymes, nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) and flavin adenine dinucleotide (FAD), to assess the metabolism of macrophages in the wound microenvironment. Inhibiting glycolysis reduced NAD(P)H mean lifetime and made the intracellular redox state of macrophages mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…OMI has also been used to classify subsets of macrophages in monoculture, tumor coculture, and in vivo in zebrafish, and to distinguish between categories of blood cells ( i.e . erythrocytes, monocytes, granulocytes, lymphocytes) ( 4244 ). Prior work also shown that NADH autofluorescence intensity increases in activated B cells compared to unstimulated B cells ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…OMI has also been used to classify subsets of macrophages in monoculture, tumor coculture, and in vivo in zebrafish, and to distinguish between categories of blood cells ( i.e . erythrocytes, monocytes, granulocytes, lymphocytes) ( 4244 ). Prior work also shown that NADH autofluorescence intensity increases in activated B cells compared to unstimulated B cells ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few works with optical metabolic imaging of the immune cells so far. For example, in 2020–2022 the group by M. Skala reported on in vitro [ 18 ] and intravital [ 26 , 27 ] studies of macrophages metabolism in normal and cancerous tissue using the intensity-based redox ratio and FLIM of NAD(P)H and FAD. Moreover, in 2021, they demonstrated the ability of autofluorescence imaging to distinguish between quiescent and activated T-cells, as well as between the subsets of CD4+ and CD8+ cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, zebrafish are more helpful in experimental replication. (3) Zebrafish embryos and larvae are transparent, which allows for real-time observations of fluorescently labeled activities inside zebrafish. , On the contrary, mouse embryos are not transparent and they naturally develop inside the mother, so currently, it is impossible to observe live embryo development or any fluorescently labeled activities in the body. Nonetheless, uses of zebrafish as an in vivo model have received many doubts and concerns, and a key question is whether the BBB of zebrafish is qualified to mimic human’s.…”
Section: Carbon Dots In Nanomedicinementioning
confidence: 99%